Osmotic dehydration of pineapple slices pre-treated by electroplasmolysis: Determination of color change kinetics - Ahsen Rayman Ergün; Yeliz Tekgül (Journal of Engineering & Processing Management, 2021)
The pineapple (Ananas comosus (L.) Merrill) is a commercial tropical fruit belonging to the Bromeliaceae family. It is rich in organic acids (citric acid, malic acid), minerals (Fe, Mg, Ca, P, K, and Zn), and vitamins (A, B1, B2, B3, and B6). Osmotic dehydration is a water removal technique by immersing the fruit in a hypertonic solution to obtain minimally processed food with a longer shelf life and high nutritional value. It can also be considered as a pretreatment that reduces the required energy inputs for convective drying and freeze-drying. Electroplasmolysis is an electrical method that is based on the growth of pores in cell membranes. It has an important effect on the dehydration and extraction processes as it increases the cell permeability and mass transfer coefficients of plant tissues. In this study, it was aimed to determine the effect of electroplasmolysis pretreatment on color change kinetics in the osmotic dehydration of pineapple slices. Electroplasmolysis was applied by a drum‐type electroplasmolyzator with 80 V/cm voltage gradient for 60 s. The osmotic dehydration process was carried out with sucrose solutions of 40, 50 and 60 ◦Bx at 20 ◦C. The processing time was 6 h in all osmotic treatments. This time was determined in preliminary experiments. Osmotically dehydrated samples with elelctroplasmolysis pretreatment and the samples without electroplasmolysis application were compared via L, a, and b values during 8 hours. The results of the study showed that fresh pineapple samples had higher L, a, and b values than both electroplasmolysis treated and untreated samples. The color values of all the samples, with and without electroplasmolysis pretreatment, decreased parallel to time increase after the osmotic dehydration process. L, a, and b values of the samples which osmotically dehydrated at 60 ◦Bx solution were higher than the color values of the samples which were dehydrated at 40 and 50 ◦Bx solutions. Lightness and yellowness were found higher in the electroplasmolysis group than the other groups. The zero-order and first-order kinetic models were used to explain the color change kinetics and it was observed that L, a, and b were fitted to a first-order kinetic model.
Keywords: pineapple; electroplasmolysis; osmotic dehydration; color; kinetic